2004
DOI: 10.1089/088282404322875421
|View full text |Cite
|
Sign up to set email alerts
|

Induction of T Lymphocytes Specific for Bovine Viral Diarrhea Virus in Calves with Maternal Antibody

Abstract: Passive antibody to bovine viral diarrhea virus (BVDV) acquired through colostrum intake may interfere with the development of a protective immune response by calves to this virus. The objective of this study was to determine if calves, with a high level of maternal antibody to bovine viral diarrhea virus (BVDV), develop CD4 + , CD8 + , or γδ T lymphocyte responses to BVDV in the absence of a measurable humoral immune response. Colostrum or milk replacer fed calves were challenged with virulent BVDV at 2-5 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 28 publications
0
24
0
2
Order By: Relevance
“…This characteristic of the vaccine may be valuable under field conditions where multiple variables can affect the process of colostrum, undoubtedly having a higher concentration of IgG1 antibodies against BVDV in it would be an advantage. Although humoral memory is an important factor in preventing and controlling BVDV infection, the scientific evidences suggest that both humoral and cell-mediated immune responses are important in protection against BVDV-induced disease in cattle [17]. To achieve this assessment, some cellular immunity parameters were studied in the vaccinated CDCs.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic of the vaccine may be valuable under field conditions where multiple variables can affect the process of colostrum, undoubtedly having a higher concentration of IgG1 antibodies against BVDV in it would be an advantage. Although humoral memory is an important factor in preventing and controlling BVDV infection, the scientific evidences suggest that both humoral and cell-mediated immune responses are important in protection against BVDV-induced disease in cattle [17]. To achieve this assessment, some cellular immunity parameters were studied in the vaccinated CDCs.…”
Section: Discussionmentioning
confidence: 99%
“…In lymphoid tissues, the cytokines secreted by T lymphocytes and other immune system cells are major determinants of class switching by B cells. Some vaccine studies with respiratory viral pathogens have shown a role of T cells in protection of young calves and have demonstrated the generation of antigen-specific T cell responses in the presence of maternal antibodies (44,67,68). A similar concept may be applied to enteric viral vaccines.…”
Section: Suppressive Effects Of Maternal (Passive) Antibodies On Immumentioning
confidence: 99%
“…Those studies used cervids that tested serologically negative for BVDV under the assumption that serologically negative equated with immunologically naive. However, we have observed in studies with cattle that exposure to BVDV when colostral antibodies are present results in a protective T cell response that is not accompanied by a serologic response Endsley et al, 2004). The objective of this study was to investigate the clinical presentation in white-tailed deer, with known BVDV exposure, following inoculation with a BVDV that had been previously isolated from white-tailed deer.…”
Section: Introductionmentioning
confidence: 99%